Evaluating pre-disaster subsidized relocations in coastal Louisiana via a game-theoretic approach - Li, Fangyuan; Jha, Pragathi; Johnson, David R. (Frontiers in Climate, 2025)
Coastal communities face increasing flood risks due to sea level rise and climate change, necessitating more proactive risk reduction strategies. Pre-disaster relocations, supported by government subsidies, offer a potentially cost-effective solution, enabling at-risk homeowners to relocate before catastrophic losses occur. This study estimates the potential effectiveness and equity implications of two pre-disaster relocation strategies using an optimization framework and high-resolution flood risk and structural data from Louisiana’s Coastal Master Plan. Our findings indicate that a total investment of about $8 billion US in pre-disaster relocations could achieve approximately $0.5 billion in flood risk reduction annually over the next 50 years, with greater benefits in later years corresponding to increasing hazard as sea levels rise. Subsidies are allocated proportionally to flood risk, ensuring procedural fairness, though potential distributional inequities remain. While pre-disaster relocation strategies improve cost-effectiveness and risk mitigation, they do not fully resolve barriers to relocation, including housing affordability, community attachment, and structural inequities in flood exposure. This study provides quantitative insights into relocation feasibility and trade-offs, informing future research on adaptive relocation strategies and equity-focused flood mitigation policies.